Research landscape of Taijiquan intervention for Hypertension hot-spot evolution and frontier analysis based on Knowledge - Zhang, Zi; Xu, Jianan; Liu, Ziyin; Li, Cuihan; Zhang, Jianwei; Lyu, Shaojun (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details